Effect of seasonal allergic rhinitis on airway mucosal absorption of chromium-51 labelled EDTA. Issue 6 (June 1993) - Greiff, L; Wollmer, P; Svensson, C; Andersson, M; Persson, C G
Abstract : BACKGROUND–Hyperpermeability of the airway mucosa is thought to be characteristic of allergic rhinitis and asthma. Nine subjects with seasonal rhinitis caused by birch pollen were studied and the nasal mucosal absorption of chromium-51 labelled EDTA was examined both in an asymptomatic period before the season and late into the season when significant allergic rhinitis symptoms were present. METHODS–A nasal pool device was used to keep a concentration of the absorption tracer in contact with a larger part of the mucosa of the ipsilateral nasal cavity. Absorption was allowed for 15 minutes and measured as the radioactivity appearing in the 24 hour urine sample. RESULTS–The nasal absorption of 51Cr-EDTA in subjects with seasonal allergic rhinitis was less during active disease than before the season. CONCLUSIONS–An airway epithelial barrier that is subject to prolonged eosinophilic inflammation may not be disrupted but may rather increase its functional tightness.